Possible association of HLA-DR and DQ Molecules with colorectal cancer in Iraqi patients - Al-Ghurabi, batool H.; sameer, ahmed; Al-Haidary, Batool; Al-Naseri, Sanaa’a; Al-Nema, Aa’meraa O.; Mousawy, Khalida M. (Journal of the Faculty of Medicine Baghdad, 2007)
Background: Human leukocyte antigen (HLA) is the most polymorphic genetic system in main.